Genotype-by-environment interaction and phenotypic stability of Musa gemplasm in West and Central Africa - Ortíz, R.; Vuylsteke, D.R.; Cauwer, I. de (1995)
A multilocational evaluation trial comprising 18 Musa genotypes was carried out from 1991to1994 in three respective locations in Humid Forest (Onne, Nigeria and M' Balmayo, Cameroon) and the Forest- Savanna Transition (Ibadan, Nigeria) zones of West and Central Africa.